Water budgeting in major rabi crops under surface irrigation in Western Indo-Gangetic Plains - CHAUDHARI, SHIV SHANKER; SUDHISHIRI, SUSAMA; KHANNA, MANOJ; DASS, ANCHAL; ROSIN, K G; BHATTACHARYA, RANJAN; MAURYA, RAGHAV (The Indian Journal of Agricultural Sciences, 2020)
A water budget confers the relationship between input, output and changes in the amount of water at an individual farm level to the watershed level depending upon point of interest. Basic components of water budgets are precipitation, evapotranspiration, change in soil moisture storage, deep percolation and runoff. However, non-availability of water balance parameter is the main problem for achieving the more crop per drop. Therefore, the current study was undertaken at ICAR-Indian Agricultural Research Institute, New Delhi farm (Mid-block, MB) during rabi 2016-17 to study the water budget of different major rabi crops (wheat, mustard, chickpea) under surface irrigation. Water budget components like soil moisture were measured by gravimetric method periodically, and daily crop-evapotranspiration (ETc) and stage-wise effective rainfall (Pe) for the test crops were estimated using FAO-CROPWAT- 8.0 model. Irrigation scheduling was done on the basis of soil moisture depletion method and total volume of water applied measured through star flow meter. The total volume of irrigation water applied during the entire crop period was 337.75, 211.54 mm and 182.90 mm, for wheat, mustard and chickpea, respectively. The results revealed that both in late- and timely - sown mustard (MB-3A-1 and 3A-2), chickpea (MB-9-A) and wheat crops (MB-3A-3, 6-A and 12-A), the highest ETc was recorded during mid-season stage (i.e. 82.90, 79.50, 94.07, 126.04, 114.02, 132.61 mm, respectively). The deep- percolation losses varied from 29.3-31.8 % for sandy loam soil to 40.2-42.2 % for clay loam soil under different crops due to larger amount of irrigation water applied in clay soil. These water budgeting parameters are location and crop specific and so to be estimated for crops, seasons and regions.